Biomarkers in the assessment of exposure and the biological effects of environmental tobacco smoke - Husgafvel-Pursiainen, Kirsti (Scandinavian Journal of Work, Environment & Health, 2002)
Environmental tobacco smoke is one of the most widespread carcinogenic exposures. Given the substantial numbers daily exposed to this substance and the great amount of scientific data on its association with chronic diseases, accurate measurements of its exposure, intake, and biological effects are needed. In fact, studies exploiting various kinds of biomarkers are crucial in increasing the understanding of the biological processes and mechanisms of the adverse health effects related to exposure, as well as in adding biological plausibility to the existing epidemiologic evidence. This paper summarizes data on known biomarkers currently in use in human population studies for detecting exposure, the biologically effective dose, the biological effects, or the disease processes related to environmental tobacco smoke. Of the biomarkers discussed, cotinine is currently well suited for assessing the exposure and intake of environmental tobacco smoke, while urinary metabolites of tobaccospecific nitrosamines appear to serve as sensitive markers for the uptake and metabolism of carcinogenic constituents of environmental tobacco smoke.
Keywords: 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone; biological effect; biomarker; cotinine; environmental tobacco smoke; exposure; genotoxicity; involuntary smoking